The interaction networks of the budding yeast and human DNA replication-initiation proteins. Issue 6 (3rd April 2019) - Wu, Rentian; Amin, Aftab; Wang, Ziyi; Huang, Yining; Man-Hei Cheung, Marco; Yu, Zhiling; Yang, Wei; Liang, Chun
ABSTRACT: DNA replication is a stringently regulated cellular process. In proliferating cells, DNA replication-initiation proteins (RIPs) are sequentially loaded onto replication origins during the M-to-G1 transition to form the pre-replicative complex (pre-RC), a process known as replication licensing. Subsequently, additional RIPs are recruited to form the pre-initiation complex (pre-IC). RIPs and their regulators ensure that chromosomal DNA is replicated exactly once per cell cycle. Origin recognition complex (ORC) binds to, and marks replication origins throughout the cell cycle and recruits other RIPs including Noc3p, Ipi1-3p, Cdt1p, Cdc6p and Mcm2-7p to form the pre-RC. The detailed mechanisms and regulation of the pre-RC and its exact architecture still remain unclear. In this study, pairwise protein-protein interactions among 23 budding yeast and 16 human RIPs were systematically and comprehensively examined by yeast two-hybrid analysis. This study tested 470 pairs of yeast and 196 pairs of human RIPs, from which 113 and 96 positive interactions, respectively, were identified. While many of these interactions were previously reported, some were novel, including various ORC and MCM subunit interactions, ORC self-interactions, and the interactions of IPI3 and NOC3 with several pre-RC and pre-IC proteins. Ten of the novel interactions were further confirmed by co-immunoprecipitation assays. Furthermore, we identified the conserved interaction networks between the yeast and human RIPs. This study provides a foundation and framework for further understanding the architectures, interactions and functions of the yeast and human pre-RC and pre-IC.